A review of maintenance service for leasing equipment - Kurniati, N; Widodo, E; Supriatna, A; Lestari, C (Institut Teknologi Sepuluh Nopember, 2018)
Recent business trend focuses more on efficiency. One of the chosen ways is leased the capital equipment from other parties. The leasing option encourages both the lessee and lessor to discuss any consequences include responsibility for managing the equipment performance, rectifying failure during operation, maintenance option provided during leasing period, as well as the accompanying cost. The review and maping of publications are conducted based on the order in which the reference appears in the publication, in order to follow the development of thinking on the research topic of leasing, yet to identify the more recent development during the last decade. Several potential research ideas could be generated from the maping toward the fast and flexibel business